The Effect of Antioxidant Vitamin C and E Administration on Spermatozoa Quality of White Rat (Rattus Norvegicus) Strain Wistar Male Against Allethrin Exposure - Faisal Yusuf Ashari; Rina Yudiwati; R.Haryanto Aswin (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Allethrin is an active ingredient used in anti-mosquito drugs. Allethrin enters the body through inhalation, allegedly can disrupt the quality of spermatozoa by decreasing its amount, motility, viability and morphology. Many studies suggested that with sufficient intake of vitamin C and E would be able to minimize free radicals caused by allethrin. This study aims to investigate the effect of giving antioxidant vitamin C and E on spermatozoa quality of white rat (Rattus norvegicus) strain Wistar male with allethrin exposure.Methods: This research was a post-test design randomized control group design using Rattus novergicus male strains Wistar exposed to allethrin (LPB IPB veterinary stem cell). A total of 16 white rat strains Wistar male divided into 4 groups, one control group (without any treatment) and 3 treatment groups (given antioxidant vitamin C, vitamin E and both). The exposure of mosquito coils was performed 8 hours per day for 45 days and on the 46th day, spermatozoa was observed. The data were analyzed using ANOVA one way and BNT.Results: The results showed that treatment with vitamins affected the amount, motility and viability of rat spermatozoa exposed to allethrin. The mean amount of control group spermatozoa and treatment was 14,93, the mean spermatozoa motility control and treatment groups were 45,13 and the mean spermatozoa viability of control and treatment groups was 58,88. This is shown by the real difference between the control group and the treatment (p <0,05). Similarly, in the control group found morphological abnormalities.Conclusion: Exposure of mosquito coils 8 hours/day for 45 days decreased the spermatozoa quality. Overall, the admission of antioxidant vitamin C and E are able to maintain the quality of spermatozoa instead of one type of vitamin.